How do you find the average rate of change of #y=2x^2-2x+1# over [-1,-1/2]?
in order to determine the average rate of change between the two usage points.
By signing up, you agree to our Terms of Service and Privacy Policy
To find the average rate of change of the function (y = 2x^2 - 2x + 1) over the interval ([-1, -\frac{1}{2}]), you can use the formula:
[ \text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a} ]
where (f(x)) is the function and (a) and (b) are the endpoints of the interval.
In this case, (a = -1) and (b = -\frac{1}{2}).
First, find (f(-1)) and (f\left(-\frac{1}{2}\right)) by substituting the respective values of (x) into the function:
[f(-1) = 2(-1)^2 - 2(-1) + 1 = 2 - (-2) + 1 = 5] [f\left(-\frac{1}{2}\right) = 2\left(-\frac{1}{2}\right)^2 - 2\left(-\frac{1}{2}\right) + 1 = 2\left(\frac{1}{4}\right) + 1 + 1 = \frac{5}{2}]
Now, substitute these values into the formula for average rate of change:
[ \text{Average Rate of Change} = \frac{\frac{5}{2} - 5}{-\frac{1}{2} - (-1)} ]
[ = \frac{\frac{5}{2} - 5}{-\frac{1}{2} + 1} ]
[ = \frac{\frac{5}{2} - \frac{10}{2}}{\frac{-1}{2} + \frac{2}{2}} ]
[ = \frac{-\frac{5}{2}}{\frac{1}{2}} ]
[ = -\frac{5}{2} \times 2 ]
[ = -5 ]
Therefore, the average rate of change of (y = 2x^2 - 2x + 1) over the interval ([-1, -\frac{1}{2}]) is (-5).
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- What is the equation of the normal line of #f(x)=-7x^3-x^2-x-1# at #x=-8#?
- How do you find the equation of the line tangent to #y=2^x# that passes through the point (1,0)?
- What is the equation of the normal line of #f(x)=x^2# at #x=-5#?
- How do you find horizontal and vertical tangent lines after using implicit differentiation of #x^2+xy+y^2=27#?
- What is the equation of the normal line of #f(x)=e^x-x^3# at #x=0#?
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7